CRISPR/Cas9-derived models of ovarian high grade serous carcinoma targeting Brca1, Pten and Nf1, and correlation with platinum sensitivity. Issue 1 (December 2017) - Walton, Josephine; Farquharson, Malcolm; Mason, Susan; Port, Jennifer; Kruspig, Bjorn; Dowson, Suzanne; Stevenson, David; Murphy, Daniel; Matzuk, Martin; Kim, Jaeyeon; Coffelt, Seth; Blyth, Karen; et al.
Abstract Transplantable murine models of ovarian high grade serous carcinoma (HGSC) remain an important research tool. We previously showed that ID8, a widely-used syngeneic model of ovarian cancer, lacked any of the frequent mutations in HGSC, and used CRISPR/Cas9 gene editing to generate derivatives with deletions inTrp53 andBrca2 . Here we have used one ID8Trp53 −/− clone to generate further mutants, with additional mutations inBrca1, Pten andNf1, all of which are frequently mutated or deleted in HGSC. We have also generated clones with triple deletions inTrp53, Brca2 andPten . We show that ID8Trp53 −/− ;Brca1 −/− andTrp53 −/− ;Brca2 −/− cells have defective homologous recombination and increased sensitivity to both platinum and PARP inhibitor chemotherapy compared toTrp53 −/− . By contrast, loss ofPten orNf1 increases growth ratein vivo, and reduces survival following cisplatin chemotherapyin vivo . Finally, we have also targetedTrp53 in cells isolated from a previous transgenic murine fallopian tube carcinoma model, and confirmed that loss of p53 expression in this second model accelerates intraperitoneal growth. Together, these CRISPR-generated models represent a new and simple tool to investigate the biology of HGSC, and the ID8 cell lines are freely available to researchers.